Protection Motivation and COVID-19 Preventive Behavior among People at Nong Pling Subdistrict Health Promoting Hospital, Mueang Nakhon Ratchasima District, Nakhon Ratchasima Province - Wichantuk, Pitsanee; Promjan, Theerapong (Srinagarind Medical Journal, 2022)
Background and Objective: The COVID-19 pandemic have affected every aspect of people’s lifestyle. This study aimed to study the level of protection motivation towards COVID-19, COVID-19 preventive behaviours and the association between factors and COVID-19 prevention behaviors Methods: This cross-sectional descriptive study consisted of 378 samples were obtained using a stratified sampling method. The research instruments were questionnaire. The data were analyzed by descriptive statistics and inferential statistics. The correlation analyzed by multiple logistic regression. Results: The results revealed that the majority of samples had perceived severity, perceived susceptibility, response efficacy expectation, self-efficacy expectation of COVID-19 at high level, 65.6, 65.9, 65.1 and 68.3, respectively. In addition, 55.3% of samples also had a good level on the COVID-19 preventive behaviours. The factors statistically significant associated with the COVID-19 preventive behaviours included age at 40 year olds and over (AOR = 2.21, 95% CI = 1.08 – 4.49), smoking (AOR = 0.28, 95% CI = 0.11 – 0.70), perceived severity of COVID-19 (AOR = 16.51, 95% CI = 5.81 – 46.93), perceived susceptibility of COVID-19 (AOR = 3.97, 95% CI = 1.21 – 13.07), response efficacy expectation in COVID-19 (AOR = 6.20, 95% CI = 2.11 – 18.23) and self-efficacy expectation in COVID-19 prevention (AOR = 3.79, 95% CI = 1.20 – 12.03). Conclusions: The results suggest that all aspect protection motivation were high significant associated with COVID-19 preventive behaviours. It is worth noting that, the COVID-19 preventive behaviours showed significant decrease among smokers. The related authorities should provide the knowledge and encourage the protection motivation to people of all age groups in community.